(untitled) - Dyché, Jill (Hoboken, N.J., 2006)
Customers are the heart of any business. But we can't succeed if we develop only one talk addressed to the 'average customer.' Instead we must know each customer and build our individual engagements with that knowledge. If Customer Relationship Management (CRM) is going to work, it calls for skills in Customer Data Integration (CDI). This is the best book that I have seen on the subject. Jill Dych? is to be complimented for her thoroughness in interviewing executives and presenting CDI.
Keywords: Customer relations,Data warehousing,Quan hệ khách hàng,Kho dữ liệu; Data processing,Xử lý dữ liệu